Metode “Fun Learning” Untuk Meningkatkan Minat Belajar Serta Kepercayaan Diri Anak - Fajar Utama Ritongga; Sarah Shahiba (Yayasan Literasi Sains Indonesia, 2022)
Learning is a process or effort made by each individual to get changes in behavior, both in the form of knowledge, skills, attitudes and positive values. However, not every individual has interest and seriousness in the learning process. This is due to several factors including the learning process that is too monotonous so it is not interesting and there are also external or environmental influences. A comfortable and good environment will support learning activities, but on the contrary if the environment is not good it will affect children's interest in learning. A lack of interest in learning was also experienced by one of the children in the NGO Community Care for Children (KOPA) where he needed help to increase his interest in learning and his confidence. The provision of assistance to children was carried out in Mini Project activities during the implementation of PKL 1, using the casework method through the general intervention stage consisting of Engagement, Intake, Contract; assessment; planning; intervention; evaluation; and termination. The focus in solving client problems is the application of fun learning methods to increase interest in learning and confidence in children. The purpose of this program was stated to be achieved, it can be seen from the increased enthusiasm for learning and also increased confidence in clients.